2019
DOI: 10.7717/peerj.7710
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of pelvic Ewing sarcoma: a SEER population-based study

Abstract: Background The pelvis is one of the primary sites of Ewing sarcoma (ES) and is associated with poorer prognoses than the extremities. Due to the rarity of this disease and limited data available, the prognostic factors of pelvic ES remain controversial. Thus, this study aimed to identify independent prognostic factors, and develop a nomogram for predicting survival rates in patients with pelvic ES. Methods Using data provided by the Surveillance, Epidemiology, and End Results (SEER) database, variables inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
2
32
0
4
Order By: Relevance
“…Furthermore, we apply subgroup analysis to demonstrate effect of surgical therapy on patient outcome among different extend of disease, surgery margin and chemotherapeutic respond. Surgical patients are reported advantage in surviving comparing to nonsurgical LC approaches based on population research (25,26). Our study reveals that patients with surgical therapy have higher PFS and LC than nonsurgical patients (PFS: RR 0.72, 95% CI: 0.61-0.86, P<0.001; LC: RR 0.72, 95% CI: 0.52-1.00, P=0.05).…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, we apply subgroup analysis to demonstrate effect of surgical therapy on patient outcome among different extend of disease, surgery margin and chemotherapeutic respond. Surgical patients are reported advantage in surviving comparing to nonsurgical LC approaches based on population research (25,26). Our study reveals that patients with surgical therapy have higher PFS and LC than nonsurgical patients (PFS: RR 0.72, 95% CI: 0.61-0.86, P<0.001; LC: RR 0.72, 95% CI: 0.52-1.00, P=0.05).…”
Section: Discussionmentioning
confidence: 66%
“…Recently, surgery has been increasingly preferred to treat pelvic ES [4]. Chen et al [5] also reported that surgical treatments are associated with better outcomes for pelvic ES. Several previous studies have compared radiotherapy to surgery, and reported surgery to be superior in terms of event-free survival, overall survival, and local control [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also found that large tumor size was an independent predictor for the presentation of lung metastasis in ES patients at initial diagnosis. Large tumor size has been consistently reported as a contributor to the poor prognosis of ES patients [ 7 , 15 , 28 , 29 ], and it also has a major influence on metastasis in ES. Hense et al identified that increased tumor size was positively associated with metastasis in patients with ES [ 30 ].…”
Section: Discussionmentioning
confidence: 99%